Descripción de la posible asociación entre cuatro competencias directivas y el cumplimiento de los indicadores de gestión de cinco gerentes de la empresa Geotecnia & Cimentaciones G&C (2017)
The present research seeks to determine the possible association between four managerial competencies and the fulfillment of the management indicators of five managers of the company Geotecnia & Cimentaciones, in Bogotá city. For this purpose, a quantitative-descriptive analysis was performed on a sample of 5 managers made up of four women in a range of 31 and 51 years of age and a 36-year-old man, Civil Engineering and specializations in finance, Organizational and occupational psychology and master's degree in geotechnics, respectively. For this measurement was used the Competence Assessment (COMPE-TEA), proposed by David Arribas and Jaime Pereña (2009).